Recent insights into near-infrared light-responsive carbon dots for bioimaging and cancer phototherapy. Issue 5 (15th April 2019) - Zhou, Bo; Guo, Zhengxi; Lin, Zhaoxing; Zhang, Lizheng; Jiang, Bang-Ping; Shen, Xing-Can
Abstract : The current developments of NIR-responsive CDs and their applications in bioimaging and phototherapy are highlighted in this review. Abstract : As a new class of near-infrared (NIR) light-responsive optical nanomaterials, NIR-responsive carbon dots (CDs) have received much attention for bioimaging and cancer therapy, because of their excellent optical properties, diverse structure, facile surface modification and good biocompatibility. In this mini review, the current developments of NIR-responsive CDs as bioimaging and phototherapy agents are summarized and highlighted, including their categorization and synthetic strategies, as well as their applications in fluorescence imaging, photoacoustic imaging, magnetic resonance imaging, and photothermal and photodynamic therapy. Moreover, a number of current challenges and perspectives on the development of NIR-responsive CDs for future cancer nanotheranostics are also discussed.